ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KETERLAMBATAN PROYEK JALAN LINGKUNGAN PERMUKIMAN DI KABUPATEN BADUNG - Ekawati, Ni Luh Yuli; Dharmayanti, GAP. Candra; Yansen, I W. (JURNAL SPEKTRAN, 2015)
In reality, the construction of local roads for housing in Badung Regency has faced barriers, which causes delay to the projects. Therefore, the projects cannot run based on the schedule. Although the constructions has been done on different road and by different contractors, the delay is still repeatedly occurred in every stage of the construction, started from the tender, constructions and post constructions stage. This study purposed to identify factors and the main factors that influence the delay of the construction of local roads for housing area. The identification was determined based on three stages of constructions. Data collection was conducted using questionnaires, involved 54 respondents those are participated in the construction of local roads for housing area in Badung Regency in 2012 and 2013.  Data analysis covered factor analysis. The result shows that there are six factors that influence delay of the construction of local roads for housing in Badung Regency. This covers: one factor at the tender stage which is the unpreparedness of the contractor’s employees; four factors at the constructions stage, which are material and time schedule, alteration and controlling, lack of labour and equipment, and financial and weather; and one factor at the post construction stage, which is the penalty for the contractors. Among these six, the main factors that cause delays are: the unpreparedness of the contractor’s employees for submitting documents to the electronic procurement (at the tender stage); lack of paving block supply (at the construction stage); and the unclear penalty for the contractors (at the post construction stage).
Keywords: project delay, the construction of local roads for housing area, factor analysis